Protein directed evolution - Laos, Roberto (2008)
Directed evolution allows us to explore protein functionalities not required in the natural environment. It mimics natural genetic processes and selective pressures. This approach is used when the molecular basis is not completely understood and rational design is a difficult task. This approach consists of serial cycles of consecutive diversification and selection which eventually lead to the accumulation of beneficial mutations. Here are presented two cases where directed evolution is used to modify two different proteins: Taq polymerase, enzyme used for DNA extension in PCR, and the LacI repressor protein which regulates gene expression on E.coli.